The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/rcs.1762
|View full text |Cite
|
Sign up to set email alerts
|

Towards human‐controlled, real‐time shape sensing based flexible needle steering for MRI‐guided percutaneous therapies

Abstract: Results endorse the feasibility and accuracy of the needle shape reconstruction and visual guidance methods developed in this work. The approach implemented for the multilayer phantom study could facilitate accurate needle placement efforts in real inhomogeneous tissues. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, there is no generally agreed value currently. According to the surgeon's clinical experience and related literature [ 36 , 37 ], select 3 mm as the accuracy limit. And this is also the minimum safety distance to protect the carotid artery for this robot system in the preoperative planning.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, there is no generally agreed value currently. According to the surgeon's clinical experience and related literature [ 36 , 37 ], select 3 mm as the accuracy limit. And this is also the minimum safety distance to protect the carotid artery for this robot system in the preoperative planning.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…3-b indicates how the amplitude of the FBG signal changes as the tool rotational velocity varies. It can be observed that the amplitude of the signal has two peaks, one at ∼24 rpm (ω 1 = 2π(0.4)) and the other ∼960 rpm (ω 2 = 2π (16)). These are the natural frequencies of the system, for which large amplitudes of the signal can be observed.…”
Section: B Experimentsmentioning
confidence: 99%
“…These studies span from complications and their respective solutions in manufacturing and design of the FBG-based sensors [9], [10], to error and output accuracy evaluation in different applications [11]- [13]. Several groups have reported work on FBG-based shape sensing of biopsy needles for measuring bending deflections of the needle in soft tissue [14]- [16]. Many groups have also studied the potential use of FBGs in shape, force and torque sensing of CMs [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, K.B.Reed et al [31] designed a robot-assisted needle steering system that uses three integrated controllers: a motion planner concerned with guiding the needle around obstacles to a target for a desired plane, a planar controller that maintains the needle in the desired plane, and a torsion compensator that controls the needle tip orientation about the axis of the needle shaft; The system can effectively improve puncture accuracy. Meng Li et al [32] proposed a real-time model updating method of needle steering in non-uniform tissue for reducing the puncture error of soft tissue; This method designs a puncture needle integrated with FBG sensor and reconstructs its tip according to the fourth-order polynomial method; Meanwhile, it also controls the puncture trajectory according to the bicycle model and combines with MRI for navigation.…”
Section: Introductionmentioning
confidence: 99%